Summary of Methodology Used in Enterotoxigenic Escherichia coli (ETEC) Challenge Experiments in Weanling Pigs and Quantitative Assessment of Observed Variability - Payton L. Dahmer; Joel M. DeRouchey; Jordan T. Gebhardt; Chad B. Paulk; Cassandra K. Jones (Kansas Agricultural Experiment Station Research Reports, 2023)
Post-weaning diarrhea in pigs can be caused by the F4 or F18 strains of enterotoxigenicEscherichia coli(ETEC). To evaluate interventions for ETEC, experimental infection via a challenge model is critical. To our knowledge, there is a lack of explanation for the variability in responses observed across ETEC challenge studies. Our objective was to quantitatively summarize the responses and variability among recent ETEC challenge studies and develop a tool for sample size calculation. The most widely evaluated response criteria across ETEC challenge studies are growth performance, fecal consistency and bacterial shedding, intestinal morphology, and immune responses. Factors that contribute to the variability seen across studies include the type of ETEC studied, dose and timing of inoculation, and the number of replications. Generally, a reduction in average daily gain (ADG) and average daily feed intake (ADFI) are seen following an ETEC challenge, as well as a rapid increase in diarrhea. Fecal bacterial shedding is a common indicator of ETEC infection, but the responses seen across the literature are not consistent due to differences in bacterial enumeration procedures. Emphasis should also be placed on the piglet’s immune response to ETEC, which is commonly assessed by quantifying levels of immunoglobulins and pro-inflammatory cytokines. Again, there is variability in these responses across published work. Small intestinal morphology is drastically altered following infection with ETEC and appears to be a less variable response criterion to evaluate. While there is a large degree of variability across ETEC challenge experiments, we have provided a quantitative summary of these studies, and a Microsoft Excel-based tool was created to help calculate sample sizes for future studies.
Keywords: Escherichia coli; literature review; weanling pigs